2013
DOI: 10.1038/ncomms3041
|View full text |Cite
|
Sign up to set email alerts
|

Two principles of organization in the prefrontal cortex are cognitive hierarchy and degree of automaticity

Abstract: The lateral prefrontal cortex is known to be organized by cognitive hierarchies following a posterior-to-anterior gradient. Here we test whether this model applies across different cognitive domains by varying levels of cognitive hierarchy in first language, second language and non-language domains. These domains vary in their degree of automaticity with first language being the most automatic. For second language/non-language a clear gradient pattern of activation depending on the level of hierarchy is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 40 publications
(48 reference statements)
6
45
0
Order By: Relevance
“…Similarly, studying the "regional co-variation" of this network in language processing tasks and tasks of nonverbal executive control should provide valuable information as to the functional (and potentially evolutionary) relationship between the human capacity for language and general reasoning and action. Importantly, this putative relationship brings with it the caveat that the involvement of pFC regions in different speech production tasks may not so much reflect executive processes as tied to speech production per se than to the various contingencies in which speech is elicited (Gherig et al, 2012;Jeon and Friederici, 2013). Future research aiming at disentangling such co-variation will face this methodological problem, necessitating careful construction of its materials and methods, as well as ecologically informed interpretation of the results.…”
Section: Summary and Future Researchmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, studying the "regional co-variation" of this network in language processing tasks and tasks of nonverbal executive control should provide valuable information as to the functional (and potentially evolutionary) relationship between the human capacity for language and general reasoning and action. Importantly, this putative relationship brings with it the caveat that the involvement of pFC regions in different speech production tasks may not so much reflect executive processes as tied to speech production per se than to the various contingencies in which speech is elicited (Gherig et al, 2012;Jeon and Friederici, 2013). Future research aiming at disentangling such co-variation will face this methodological problem, necessitating careful construction of its materials and methods, as well as ecologically informed interpretation of the results.…”
Section: Summary and Future Researchmentioning
confidence: 85%
“…Of highest importance is the necessity to establish the functional-anatomic relationships between the various executive components of pFC and posterior primary and multisensory regions engaged in phonological perception and storage, lexical-conceptual memory and sensorimotor interface (Hickok and Poeppel, 2007), as well as other abilities often deemed 'peripheral' to language processing such as reading (Dehaene and Cohen, 2011), music (Uddén and Bahlmann, 2012) or bilingualism (Bialystok, 2009;Jeon and Friederici, 2013). In the mean time, this discussion hopefully shows the theoretical and empirical import of a comprehensive picture of the frontal lobe as the main executive component of human language.…”
Section: Summary and Future Researchmentioning
confidence: 99%
“…This effect was likely due to the extensive piano experience of the participant and the concurrent acquisition of neuronal mechanisms in Broca's area that represent action hierarchy. Based on the findings by Rüschemeyer et al (2006), as well as Jeon and Friederici (2013), it is conceivable that Broca's area is not necessarily activated by processing a simple hand motion action. Rather, Broca's area may come into play only when processing an unfamiliar hand motion sequence.…”
Section: Discussionmentioning
confidence: 98%
“…However, BA 44 of non-native speakers is consistently active, regardless of the degree of complexity of sentences (see also Rüschemeyer et al, 2005; Yokoyama et al, 2006). Moreover, Jeon and Friederici (2013) demonstrated that the syntactical analysis of complex non-native sentence recruited BA 47. Thus, only BA 44 of native speakers showed complexity-dependent activation.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of this skill coincides with structural maturation of dorsal language tracts in the brain (Brauer, Anwander, Perani, & Friederici, 2013). These tracts interconnect lower-level regions of the Perception-Action Cycle (Jeon & Friederici, 2013) and support sound-to-motor mapping in adults (Saur et al, 2008). We hypothesise that these dorsal tracts -and the cortical regions they connect -become increasingly involved in language processing as skills become automatised during childhood (at least for relatively simple language skills).…”
Section: Increasing Activation In Sensory and Motor Regions: Languagementioning
confidence: 94%